2021
DOI: 10.1016/j.mjafi.2021.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Seroconversion among COVID-19 patients admitted in a dedicated COVID hospital: A longitudinal prospective study of 1000 patients

Abstract: Background The immune response after SARS-CoV-2 is complex and may be affected by severity of the disease, race, etc. The present study was conducted to assess the serial antibody response among the COVID-19 patients admitted in the hospital. Methods The study was conducted between July and October 2020 in a dedicated COVID-19 hospital. All consented patients underwent serial testing of antibodies using a rapid chromatographic immunoassay-based qualitative IgG/IgM kit e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
1
8
1
Order By: Relevance
“…As expected, the antibody titers significantly increased over the time, reaching the almost complete seroconversion to IgG, about 17–19 days after symptoms onset. This is in line with reports from the literature, concluding that the rate and timing of IgM and IgG seroconversion were inconsistent across the independent analyzed studies, but most seroconverted for IgG within 2 weeks and 100% within 4 weeks (O Murchu et al 2020 ; Yadav et al 2021 ).…”
Section: Discussionsupporting
confidence: 89%
“…As expected, the antibody titers significantly increased over the time, reaching the almost complete seroconversion to IgG, about 17–19 days after symptoms onset. This is in line with reports from the literature, concluding that the rate and timing of IgM and IgG seroconversion were inconsistent across the independent analyzed studies, but most seroconverted for IgG within 2 weeks and 100% within 4 weeks (O Murchu et al 2020 ; Yadav et al 2021 ).…”
Section: Discussionsupporting
confidence: 89%
“…These may be false-negative or evidence that these are early infections with levels of antibodies that cannot be detected by the serological tests we used [35]. Moreover, it could be related to seroconversion, a period the onset of antibody production which will the rise to detectable [57], [58]. In addition, numerous studies have already reported a low sensitivity of the COVID IgM/IgG serological tests compared to techniques such as ELISA or LUMINEX [59]- [63] suggesting a continuous readaptation of prefabricated RDTs in the emergency anti-COVID response is needed, especially as circulating strains arise and cause new waves.…”
Section: Discussionmentioning
confidence: 97%
“…These may be false negatives or evidence that these are early infections with levels of antibodies that cannot be detected by the serological tests we used [ 36 ]. Moreover, it could be related to seroconversion, a period before the onset of antibody production, which will increase detectability [ 56 , 57 , 58 ]. In addition, numerous studies have already reported low sensitivity of COVID IgM/IgG serological tests compared to techniques such as ELISA or LUMINEX [ 59 , 60 , 61 , 62 , 63 ], suggesting a continuous readaptation of prefabricated RDTs in the emergency anti-COVID response is needed, especially as circulating strains arise and cause new waves.…”
Section: Discussionmentioning
confidence: 99%